Alpha-Mangostin Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice Partly Through Activating Adenosine 5'-Monophosphate-Activated Protein Kinase - Ren-shi Li; Ren-shi Li; Gong-hao Xu; Juan Cao; Bei Liu; Hai-feng Xie; Yuji Ishii; Chao-feng Zhang; Chao-feng Zhang (Frontiers Media S.A., 2019)
Background: Pulmonary fibrosis (PF) is a devastating interstitial lung disease and characterized by an abnormal accumulation of extracellular matrix (ECM). Nintedanib (NDN) and pirfenidone are two approved therapies for PF, but their potential side-effects have been reported. Recently, the use of natural supplements for PF is attracting attention. Alpha-mangostin (α-MG) is an active xanthone-type compound isolated from the nutritious fruit mangosteen.Purpose: In the present study, the potential effect and underlying mechanism of α-MG were evaluated in bleomycin (BLM)-induced PF and activated primary lung fibroblasts (PLFs).Methods: Histopathological changes and collagen deposition were analyzed via hematoxylin-eosin staining and Masson staining, the expression of nicotinamide adenine dinucleotide phosphate oxidase-4 (NOX4) involved in oxidative stress in lung tissues was analyzed by immunochemistry staining. The expressions of α-smooth muscle actin (α-SMA), collagen I (Col I), p-adenosine 5'-monophosphate-activated protein kinase (AMPK)/AMPK, and NOX4 were detected by Western blot, immunofluorescence or RT-PCR, and effects of α-MG on cell viability were detected using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide.Results:In vivo results demonstrated that α-MG treatment (10 mg/kg/day) significantly ameliorated BLM-induced deposition of ECM in lung tissues. Moreover, α-MG could inhibit protein expressions of α-SMA and Col I as well as its mRNA levels. In addition, α-MG also significantly inhibited transforming growth factor-β1/Smad2/3 pathway and regulated the protein expression of matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 in lung tissues. In vitro results demonstrated that α-MG significantly increased p-AMPK/AMPK but reduced the protein expression level of α-SMA and Col I as well as NOX4 in activated PLFs. Further study demonstrated that these improvement effects were significantly blocked by compound C.Conclusion: α-MG treatment significantly decreased oxidative stress in lungs partly by activating AMPK mediated signaling pathway in BLM-induced PF and activated PLFs and decreased the deposition of ECM. The present study provides pharmacological evidence to support therapeutic application of α-MG in the treatment of PF.